Assessing the Relevance of Social Return on Investment (SROI) as a Method of Impact Assessment - Case Study of Hindustan Unilever Ltd. (International Journal of Food and Nutritional Sciences, 2022)
With the increased need for sustainability and conscious business practices, companies are altering operational capabilities for good. There arises a need to monitor and assess the impact of these practices on surroundings and stakeholders in order to evaluate the deviation from the set standard. This paper explores the relevance of Social Return on Investment (SROI) as a method of evaluating sustainable business practices for companies. The paper further highlights the use of SROI to measure the impact of business practices of Hindustan Unilever Limited and gauges the benefits in impact measurement.